ئامادەکردنى پڕۆگرامێک بۆ بابەتى دەرونناسى هونەر لە بەشى پەروەردەى هونەرى کۆلێژى پەروەردەى بنەڕەتى/ زانکۆى سلێمانى - حسين, پ.د. نظام عبدالجبار; حمەصالح, ى.ت. ستیڤان نصرالدین (Sulaimani Journal for Humanities, 2023)
The research aimed at developing a curriculum for the Art Psychology subject in the Art Education Department of the College of Basic Education at the University of Sulaimani. According to the nature and objectives of the study, a descriptive approach is adopted. The research population was the subject of Art Psychology in general and the sample consisted of several subjects of the population, namely: Artistic Creativity, Analysis of Artistic Work and Art Therapy, which are selected purposively on the basis of art, psychology and education fields according to the experts. To determine the content of the curriculum, the researcher prepared an open questionnaire. Following the experts’ opinions in the open questionnaire, a closed questionnaire form of (20) items was created incorporating the content of the curriculum. The form was distributed to a number of experts (19 experts) who were requested to evaluate the appropriateness and inappropriateness of the items and comment on any note or linguistic error in the note section. To ensure the scientific nature of the questionnaire, its validity was established, and (94%) of the subjects were considered appropriate. Afterwards, the researcher began to implement building the curriculum procedures based on the camp design model, which constitutes the conclusions of the study, and the research was concluded with some recommendations.